Analysis of ASN and TNI pension customer visit services at Bank Woori Saudara Kc Solo - Hartanti, Nanda Febriana Dila; Sari, Dhany Efita (Manajemen dan Bisnis, 2025)
The rapid development of information and communication technology has significantly changed the financial sector, especially through digital banking. Indonesia ranks third in the world in terms of digital banking usage, hence the need understand its challenges and opportunities, which is crucial for the sustainability of the financial industry. The study fills a research gap by addressing the unique challenges faced by pension customers in adapting to digital banking services. This research aims to analyze the ASN and TNI pension customer visit service system at Bank Woori Saudara KC Solo, analyze the obtacles faced, and analyze the impact of these services on customer satisfaction. The research used a qualitative approach with a case study design, involving in-depth interviews, observation and documentation. The results show that the mechanism implemented contributes positively to customer satisfaction, with staff friendliness and attentiveness as key factors. However, there are challenges such as accessibility and time constraints. For the future research, it is recommended to expand the scope of research to several other banks and involve more informants, as well as explore other factors that may affect customer satisfaction in more depth. Can use a mixed-methods approach, combining quantitative surveys to measure customer satisfaction with qualitative interviews to explore underlying perceptions. Could explore the impact of technology interventions, such as AI-driven customer support, on the satisfaction of pension customers.